2013
DOI: 10.1097/01.aids.0000432459.36970.a9
|View full text |Cite
|
Sign up to set email alerts
|

Variations at multiple genes improve interleukin 28B genotype predictive capacity for response to therapy against hepatitis C infection

Abstract: A number of genetic factors modify the predictive capacity of IL28B genotype. These can be used to identify HCV genotype 1 or 4-infected patients with a very high or a very low probability to respond to bitherapy with Peg-IFN/RBV. Predictive models based on these factors could be helpful to tailor direct acting antiviral-based therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The epistatic interaction between IL28B and the SNPs located in LDLR rs14158, rs11672123, rs1433099 and rs2569540 of LDLR on SVR has been previously communicated by our group, 11,12 and this study clarifies the influence of LDLR genetics in HCV replication.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The epistatic interaction between IL28B and the SNPs located in LDLR rs14158, rs11672123, rs1433099 and rs2569540 of LDLR on SVR has been previously communicated by our group, 11,12 and this study clarifies the influence of LDLR genetics in HCV replication.…”
Section: Discussionsupporting
confidence: 70%
“…This association with VLDL allows the virus to bind target cells through lipoprotein receptors 7 after partial processing by lipoprotein and hepatic lipase, which hydrolyze the triglycerides in the VLDL giving rise to IDL and lowdensity lipoprotein (LDL). Experimental 8 and clinical 9 data suggest that LDL receptor (LDLR) is a docking molecule or a co-receptor for HCV: (1) the levels of HCV RNA in primary hepatocytes correlate with LDLR mRNA expression and LDL uptake efficiency; 10 (2) soluble LDLR can inhibit HCV infectivity; 10 (3) greater plasma LDL levels are associated with sustained virological response (SVR) after treatment with Peg-IFN plus RBV, likely due to competitive block of the HCV entry; 11 (4) polymorphisms in LDLR, which are associated with plasma levels of LDL, have a synergistic impact on the likelihood of achieving SVR with Peg-IFN plus RBV in patients infected with viral genotypes 1 and 4 11,12 as well as on viral kinetics after treatment. 13 However, some discrepancies remain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it has been suggested that patients with familial hypercholesterolemia due to mutations in the LDLR gene may be protected against HCV infection 15 . Indeed, polymorphisms linked to LDLR have been associated with Hepatitis C viral load 16 and with the capacity for responding to interferon-based antiviral therapy 1720 . Thus, it could be hypothesized that a dysfunction of LDLRAP1 would affect to the capacity of LDLR to favour the entry of HCV or, alternatively, it could interfere with the metabolic requirements of the HCV life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…These individuals have been used as controls in several genome-wide association studies (GWASs) 2729 . The HCV-infected group I was constituted by HCV chronically infected individuals who consecutively initiated a pegylated interferon plus ribavirin treatment from May 2000 to December 2010 in the Infectious Diseases Units of 5 tertiary care hospitals in Spain and who were genotyped for 116 SNPs 16,17,30 .…”
Section: Methodsmentioning
confidence: 99%